Logarithmically Improved Blow up Criterion for Smooths Solution to the 3D Micropolar Fluid Equations - Yin-Xia Wang; Hengjun Zhao (Journal of Applied Mathematics)
Blow-up criteria of smooth solutions for the 3D micropolar fluid equations are investigated. Logarithmically improved blow-up criteria are established in the Morrey-Campanto space.